Etiology and prognosis of pregnancy-related pelvic girdle pain; design of a longitudinal study - Kroese Mariëlle EAL; Heuts Annie; Bastiaenen Caroline HG; de Bie Rob A; Bastiaanssen Janneke M; Essed Gerard GM; van den Brandt Piet A (BMC, 2005)
Abstract Background Absence of knowledge of pregnancy-related pelvic girdle pain (PPGP) has prompted the start of a large cohort study in the Netherlands. The objective of this study was to investigate the prevalence and incidence of PPGP, to identify risk factors involved in the onset and to determine the prognosis of pregnancy-related pelvic girdle pain. Methods/design 7,526 pregnant women of the southeast of the Netherlands participated in a prospective cohort study. During a 2-year period, they were recruited by midwives and gynecologists at 14 weeks of pregnancy. Participants completed a questionnaire at baseline, at 30 weeks of pregnancy, at 2 weeks after delivery, at 6 months after delivery and at 1 year after delivery. The study uses extensive questionnaires with questions ranging from physical complaints, limitations in activities, restriction in participation, work situation, demographics, lifestyle, pregnancy-related factors and psychosocial factors. Discussion This large-scale prospective cohort study will provide reliable insights in incidence, prevalence and factors related to etiology and prognosis of pregnancy-related pelvic girdle pain.